1983
DOI: 10.1111/j.1365-2710.1983.tb01058.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of a New Antacid Formulation Based on Magaldrate

Abstract: SUMMARY A new antacid formulation (Dynese) based on magaldrate, a discrete chemical entity with marked antacid properties, has been compared in vitro with several commercially available antacid preparations. All preparations were tested for their ability to maintain gastric pH within acceptable limits and to effectively bind bile acids. Sodium concentrations were also determined. Dynese was shown to compare very favourably with existing preparations in that it had a prolonged even neutralization profile, effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…On the other hand, the magaldrate efficacy in the treatment of gastroesophageal reflux could be mainly attributed to its ability to rise rapidly and consistently the intragastric pH [22,35]. However, other studies have reported that magaldrate is also able to inactivate pepsin and binding to bile acids and lysolecithin, aggressors in case of gastroesophageal reflux [35,36]. Furthermore, magaldrate activates other gastroprotective mechanisms, such as, increment in gastric mucus secretion [37], stimulation of endogenous prostaglandin E 2 [38] and protection of gastric mucosa of lipid peroxidation [39].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the magaldrate efficacy in the treatment of gastroesophageal reflux could be mainly attributed to its ability to rise rapidly and consistently the intragastric pH [22,35]. However, other studies have reported that magaldrate is also able to inactivate pepsin and binding to bile acids and lysolecithin, aggressors in case of gastroesophageal reflux [35,36]. Furthermore, magaldrate activates other gastroprotective mechanisms, such as, increment in gastric mucus secretion [37], stimulation of endogenous prostaglandin E 2 [38] and protection of gastric mucosa of lipid peroxidation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Ант ациды и алгинаты могут применяться как в качестве монотерапии редкой изжоги, не сопровождающейся развитием эзофагита, так и в схемах комплексной терапии ГЭРБ, так как оказываются эффективны в быстром устранении симптомов [124,125] (УУР А, УДД -1).…”
Section: консервативное лечениеunclassified
“…Комбинированный препарат, содержащий магалдрат и симетикон, способен быстро нейтрализовать соляную кислоту и длительно поддерживать стабильный уровень pH, очень активно связывать соли желчных кислот [125]. При его применении наблюдается исчезновение симптомов у большинства пациентов с ГЭРБ [129] (УУР А, УДД -1).…”
Section: консервативное лечениеunclassified